2020
DOI: 10.3390/agronomy10070962
|View full text |Cite
|
Sign up to set email alerts
|

Rotation, Mulch and Zero Tillage Reduce Weeds in a Long-Term Conservation Agriculture Trial

Abstract: Weed management is one of the main challenges of conservation agriculture. Although all three components of conservation agriculture (minimal tillage, permanent soil cover and crop diversification) can reduce weed populations, these effects may only become apparent in the medium to long term. This study evaluated weed biomass, density and diversity with and without herbicide control in a long-term trial initiated in 1991 in the Mexican Highlands to evaluate all three components of conservation agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Liebman and Dyck (1993) reported contrasting findings in their literature survey where in 21 cases out of 27 there were fewer weeds in crop rotations than in monoculture. In several studies, crop rotation is reported to be an effective tool to control weeds (Mertens et al, 2002;Zawislak and Kostrzewska, 2005;Fonteyne et al, 2020). However, Bárberi and Cascio (2001) reported that crop rotation only slightly decreased major weed species abundance when tillage had a large negative influence on weed seedbank size, as was the case in our study where plowing was a more effective tool to control weeds than crop rotation.…”
Section: Effect Of Crop Rotation On Weedsmentioning
confidence: 41%
See 1 more Smart Citation
“…Liebman and Dyck (1993) reported contrasting findings in their literature survey where in 21 cases out of 27 there were fewer weeds in crop rotations than in monoculture. In several studies, crop rotation is reported to be an effective tool to control weeds (Mertens et al, 2002;Zawislak and Kostrzewska, 2005;Fonteyne et al, 2020). However, Bárberi and Cascio (2001) reported that crop rotation only slightly decreased major weed species abundance when tillage had a large negative influence on weed seedbank size, as was the case in our study where plowing was a more effective tool to control weeds than crop rotation.…”
Section: Effect Of Crop Rotation On Weedsmentioning
confidence: 41%
“…Tillage influences insect pests variably, depending on their life history strategies, i.e., growth, reproduction, survival, and dispersal (Stinner and House, 1990;Andersen, 1999). Different soil management and cultivation techniques also favor different weed species (Fonteyne et al, 2020). Non-tillage can also impact soil organic carbon sequestration as well as disease suppression and microbial biomass in soil (Palojärvi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Woźniak (2018), populations of annual grass increase in no-tillage systems concurrent with a decrease in populations of dicotyledonous weeds. Again, Fonteyne et al (2020) observed annual and perennial grasses, and perennial dicot species would increase, and annual dicot species would decrease in reduced tillage. Moreover, Moonen and Barberi (2004) recorded fivefold higher seedbank density in reduced tillage systems compared to full tillage systems.…”
Section: Introductionmentioning
confidence: 84%
“…CA is being promoted globally for improving soil health; sustainably increase the overall economic productivity of mechanized agriculture (Sanyal et al 2008). In addition to agronomic benefits, CA also has a major influence on the relative abundance of weed species (Fonteyne et al 2020), and weed control is perceived as one of the most challenging issues due to a reduction in tillage operations. The composition and dynamics of weeds in the soil weed seedbank under minimum tillage was found to be changed compared to conventional tillage (Pittelkow et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Zero tillage increased yields in 2018 in Teopoxco and possibly in 2018 and 2019 in Tamazulapam, although due to the trial design it is impossible to rule out fertilization or planting density effects. Zero tillage did save an average 8 labor days per hectare in land preparation for maize and might in the long term reduce labor costs associated with weed control (Fonteyne et al, 2020), especially if combined with relay cropped peas. Reduced over the course of the trials from originally high levels, labor costs can still be lowered, for example by using animal-or two-wheel-tractordrawn seeders, which would cut the time for sowing from 11.5 to 2.0 days per hectare while improving the quality of sowing and fertilization (Van Loon et al, 2020).…”
Section: Cyclementioning
confidence: 99%